Effects of Phenology-based Irrigation Scheduling and Nitrogen on Light Interception, Water Productivity and Energy Balance of Maize (Zea mays L.) - Ashwani Kumar, Gouranga Kar and (Journal of the Indian Society of Soil Science, 2015)
Maize (Zea mays L.) is considered as one of the diversifying options in rice fallows of eastern India. Research was conducted to study intercepted photosynthetically active radiation (IPAR), radiation utilization efficiency (RUE), latent heat flux and water productivity of the crop under different irrigation (120, 180, 240, 300 and 360 mm) and nitrogen (30, 60, 90, 120 and 150 kg N ha-1) levels and relationships were established among biomass, yield, RUE, IPAR and water productivity. The RUE of the crop ranged from 1.01 to 2.16 g MJ-1, the latent heat flux from 8.64 to 18.77 MJ m-2 day-1 and average water productivity from 0.673 to 0.983 kg m-3 under different N and irrigation levels. The difference in LAI, biomass production and yield was not significant between 120 and 150 kg N ha-1, which might be attributed to the fact that these crop attributes were not proportionately increased with the amount of additional N applied. A comparison of water productivity between the treatments receiving irrigation at flowering and milk ripe-grain filling stages and not receiving irrigations at these stages with same amount of irrigation (300 mm) showed that water was more efficiently utilized when irrigation was not skipped at flowering and milk ripe-grain filling stages. The RUE was higher in milk ripe stage (milk to solid conversion of endosperm, but whole kernel content is still milky liquid) and reduced during grain filling stage. This might be attributed to the reduced seed weight and grain number in case of water and N stressed plots, where partitioning of photosynthates towards grain is less that limits the RUE.